THE EFFECT OF WORKLOAD, RELATIONSHIPS WITH SUPERIORS AND MOTIVATION ON JOB SATISFACTION - Devi, Shinta Prasetia; Haribowo, Siget Fitrianto; Sopiah (Universitas Negeri Surabaya, 2025)
This study investigates the influence of workload, supervisor relationships, and work motivation on employee job satisfaction in the subcontracting sector. Utilising a quantitative research design with multiple linear regression analysis, the study aims to understand how these three variables interact and impact overall job satisfaction. The results indicate that workload negatively affects job satisfaction, suggesting that excessive work demands may reduce employee morale and contentment. Conversely, positive relationships with supervisors and strong work motivation are found to significantly enhance job satisfaction. Among the three variables, motivation stands out as the most influential factor, highlighting its central role in shaping employee attitudes and performance. The findings suggest that organisations should strive to balance workload effectively, cultivate supportive and respectful supervisory relationships, and implement strategies that strengthen intrinsic motivation. These may include recognition programs, career development opportunities, and meaningful work assignments. By addressing these key areas, companies can foster a more positive work environment that not only supports employee well—being but also enhances organisational productivity and retention. The study provides valuable insights for human resource management, particularly in subcontracting settings where job satisfaction can be a critical factor in maintaining performance and reducing turnover. This research contributes to the broader understanding of employee satisfaction drivers in dynamic and competitive industries.